Crosstalk of HgCdTe LWIR n-on-p diode arrays - 孙英会 张波 于梅芳 廖清君 张燕 文鑫 姜佩璐 胡晓宁 戴宁 (Journal of semiconductors, 2009)
Crosstalk of HgCdTe long-wavelength infrared （LWIR） n-on-p diode arrays was measured using scanning laser microscopy. During the measurement, HgCdTe diode arrays with different diode pitches were frontside illuminated by a He-Ne laser at liquid nitrogen temperature and room temperature. The experimental results show that crosstalk between the nearest neighboring diodes decreases exponentially as the diode pitch increases, and the factors that affect the obtained crosstalk are presented and analyzed. Crosstalk out of the nominal diode area （optically sensitive area） is also measured and discussed.